Geriatric Assessment of Physical and Cognitive Functioning in a Diverse Cohort of Systemic Lupus Erythematosus Patients: A Pilot Study. Issue 10 (27th August 2018) - Plantinga, Laura; Tift, Benjamin D.; Dunlop‐Thomas, Charmayne; Sam Lim, S.; Barrett Bowling, C.; Drenkard, Cristina
Abstract : Objective: To use multidomain functional assessment, which is commonly performed in geriatric patients but is novel in patients with systemic lupus erythematosus (SLE), to better understand functional impairment in patients with SLE. Methods: We recruited 60 adult participants (aged 20–39 years [26.7%], 40–59 years [50.0%], and ≥60 years [23.3%]; 80.0% African American and 90.0% female) from an existing cohort of SLE patients. During in‐person visits (from October 2016 to April 2017), we evaluated physical performance (range 0–4, with higher scores indicating better performance), cognitive performance (5 fluid cognition domains; adjusted T scores), and self‐reported measures including physical functioning (T scores), activities of daily living (ADLs), falls, and life‐space mobility. Results: In the SLE patients, the mean balance score (3.7) and gait speed score (3.4) were high, while the mean lower body strength score was low (1.8). Cognitive performance was average (score of 5.0) for episodic (47.7) and working (48.6) memory and low average for cognitive flexibility (43.7), processing speed (42.6), and attention/inhibitory control (38.8 [>1 SD below average]) when compared with healthy individuals of the same age, sex, race, ethnicity, and education level. Most participants reported the ability to independently perform basic ADLs, but many reported the inability to independently perform instrumental ADLs. Nearly half (45.0%) of participants reported falling in the prior year. Only 40.0% reported unlimited ability to travel without the help of another person. Scores generally did not differ substantially according to age. Conclusion: Our results suggest a high prevalence of impairment across multiple domains of function in SLE patients of all ages, similar to or exceeding the prevalence observed in much older geriatric populations. Further research into the added value of geriatric assessment in routine care for SLE is warranted.